Antagonism of the genera Penicillium and Aspergillus, rhizospheric isolates of Giant Cardon (Pachycereus pringlei) against phytopathogenic fungi (Bioagro, 2025)
Aspergillus sp. and Penicillium sp. are fungi widely studied for their biotechnological applications. In the agricultural field, their benefical characteristics make them an attractive alternative source for biological disease control. Cacti, such as the giant cardon (Pachycereus pringlei) group a great diversity of this type of desert species that have greater metabolic action, due to their resistance to extreme environments. However, there are few studies on this subject. The objective of this research was to isolate, identify and evaluate the antagonism of Penicillium sp. and Aspergillus sp. isolated from the rhizosphere of giant cardon against phytopathogenic root fungi. Forty soil samples were collected from the rhizosphere of cardon, at 30 cm depth in four sites in the municipality of La Paz, Baja California Sur. The population and diversity were calculated and the purified isolates were identified macroscopically and microscopically. The pathogenicity of the isolates was determined by inoculation in tomato fruits. While the antagonism was evaluated through dual culture, with Fusarium oxysporum, Fusarium solani and Rhizoctonia solani. The results were recorded in all the agroecosystems evaluated a higher population of Penicillium sp. than Aspergillus sp. (5 versus 2 isolates). The most abundant species was P. digitatum. The antagonism showed significant differences (p≤0.05) between isolates of the same genus (different species), presenting up to 70% mycelial inhibition. While in the pathogenicity test, two Penicillium isolates and one Aspergillus isolate showed a greater effect than the rest. This information confirms the capacity of Aspergillus sp. and Penicillium sp. in the control of plant pathogens.
Keywords: Biocontrol; diversity; efficacy; microorganisms